“Evaluation of the effect of nutrition and oral hygiene on Dmft index of patients applying to restorative dentistry clinic” - Rahime Zeynep Erdem; Fatih Bedir (BMC Public Health)
Abstract Objectives The aim of this study was to investigate the effects of diet, oral hygiene, visits to the dentist, and body mass index (BMI) on the risk of dental decay. Methods 240 patients aged 18–50 were included in the study. Participants completed a questionnaire that included demographic information and oral hygiene habits. They were also required to submit dietary analysis forms, which asked about the foods and amounts consumed at breakfast, lunch, dinner, and during two snacks. Intraoral and radiographic examinations of the patients were performed, and the values for DMFT, plaque index, dental calculus index, and oral hygiene index (OHI-S) were recorded. Statistical analysis, including Chi-square tests, independent samples t-tests, and one-way ANOVA, was conducted on the data (p < 0.05). Results The oral hygiene index(OHI-S) was determined to be good in 58.3% of the study participants and poor in 10%. No statistical difference was found between BMI and DMFT index (p > 0,005). When the relationship between food consumption frequencies and DMFT was evaluated, it was determined that there was no statistically significant relationship between bread, rice, milk, legumes, and DMFT values (p > 0,005), but there was a statistically significant relationship between fruit, vegetables, yoghurt, cheese, meat/chicken/fish, eggs, honey, sugar, glutens, acidic drinks, tae/coffee consumption and DMFT indices (p < 0,005 ). Conclusion The types of food consumed by patients and the frequency of consumption affect the risk of caries.